STUDYING LANDSLIDES IN THUA THIEN - HUE PROVINCE - Tan, Mai Thanh; Tao, Nguyen Van (Vietnam Journal of Earth Sciences, 2014)
Studying landslide hazards in Thuathien - Hue is based on the relationship between landslide and its controlling factors (topographical slope, rainfall, landuse, weathering crust, lithological properties, fault and road proximity), evaluated in a key areas. This relationship is quantified by weighting the classes in each factor and weighting each factor in a set of landslide-controlling factors. This is the bases for landslide susceptibility mapping given by integrating the weighted factor maps. The class is weighted by its landslide density, normalized on a 1-to-9 scale. The factor weighting is determined based on the landslide quantity, which would be engendered in a whole province with considering thelandslide density in each class as that obtained from the key area. The calculated results show that, influences of landslide-controlling factors in Thuathien - Hue may increase in following order: road proximity, landuse, weathering, fault, lithology, rainfall, and slope. The areas of very low, low, medium, high and very high landslide hazards accountrespectively 12,36%, 15,34%, 39,69%, 31,89% and 0,82% of province. The high and very hazards are distributed in linear form, suggesting a strong influence of faults in these areas.ReferencesAyalew L., Yamagishi H. and Ugawa N., 2004. Landslide susceptibility mapping using GIS in Tsugawa area of Agano River, Niigata Prefecture, Japan. Landslides, 1, 73-81.Ayalew L., and Yamagishi H., 2005. The application of GIS-based logistic regression for landslide susceptibility mapping in the Kakuda - Yahiko Mountains, Centrall Japan. Geomorphology 65. 15-31.Guzzetti F., Carrara A., Cardinali M. and Reichenbach P., 1999. Landslide hazard evaluation : a review of current techniques and their application in a multi-scale study, Central Italy. Geomorphology 31, 181-216.Phạm Văn Hùng, Nguyễn Xuân Huyên, 2010. Đánh giá hiện trạng và phân vùng cảnh báo nguy cơ trượt lở đất thành phố Đà Nẵng. Tạp chí Các KH về TĐ, T.32, (2), 106-113.Phạm Văn Hùng, 2011. Đánh giá hiện trạng và phân vùng cảnh báo nguy cơ trượt lở đất tỉnh Quảng Nam. Tạp chí Các KH về TĐ, T.33, 3ĐB, 518-525.Pachauri AK, Gupta PV, Chander R, 1998. Landslide zoning in a part of the Garhwal Himalayas. Environ. Geol. 36 (3-4), 325-334.Saaty Thomas, 1994. Fundamental of decision making and priority theory with analytic hierarchy process. Pittsburgh: RWS publication, 527p.Schuster R.L., 1996. Socioeconomic significance of landslides. In Landslides: investigation and mitigation, ed. A.K. Turner, R.L. Schuster, p. 12-35. Washington: National Academy Press.Shaban A., Khawlie M., Bou Kheir R., Abdallah C., 2001. Assessment of road instability along a typical moutainous road using GIS and aerial photos, Lebanon, Eastern Mediterranean. Bulletin of Engineering Geology and Environment 60, 93-101.